Candida albicans quorum-sensing molecule farnesol modulates staphyloxanthin production and activates the thiol-based oxidative-stress response in Staphylococcus aureus. Issue 1 (1st January 2019) - Vila, Taissa; Kong, Eric F.; Ibrahim, Ahmed; Piepenbrink, Kurt; Shetty, Amol C.; McCracken, Carrie; Bruno, Vincent; Jabra-Rizk, Mary Ann
ABSTRACT: Microbial species utilize secreted-signaling molecules to coordinate their behavior. Our previous investigations demonstrated a key role for the Candida albicans -secreted quorum-sensing molecule farnesol in modulating Staphylococcus aureus response to antimicrobials in mixed biofilms. In this study, we aimed to provide mechanistic insights into the impact of farnesol on S. aureus within the context of inter-species interactions. To mimic biofilm dynamics, farnesol-sensitized S. aureus cells were generated via sequential farnesol exposure. The sensitized phenotype exhibited dramatic loss of the typical pigment, which we identified as staphyloxanthin, an important virulence factor synthesized by the Crt operon in S. aureus . Additionally, farnesol exposure exerted oxidative-stress as indicated by transcriptional analysis demonstrating alterations in redox-sensors and major virulence regulators. Paradoxically, the activated stress-response conferred S. aureus with enhanced tolerance to H2 O2 and phagocytic killing. Since expression of enzymes in the staphyloxanthin biosynthesis pathway was not impacted by farnesol, we generated a theoretical-binding model which indicated that farnesol may block staphyloxanthin biosynthesis via competitive-binding to the CrtM enzyme crucial for staphyloxanthin synthesis, due to high structural similarity to the CrtM substrate. Finally, mixed growth with C. albicans was found to similarly induce S. aureus depigmentation, but not during growth with a farnesol-deficient C. albicans strain. Collectively, the findings demonstrate that a fungal molecule acts as a redox-cycler eliciting a bacterial stress response via activation of the thiol-based redox system under the control of global regulators. Therefore, farnesol-induced transcriptional modulations of key regulatory networks in S. aureus may modulate the pathogenesis of C. albicans-S. aureus co-infections.